Post-morality : Cambridge Darkroom and Kettle's Yard 1990 open exhibition. - Cambridge Darkroom; Kettle's Yard Gallery, Cambridge (Cambridge : Cambridge Darkroom, 1990)
Anderson, Gary ; Bewley, Jon ; Bidewell, Dilys ; Brennan, Tim ; Burns, Bill ; Charnley, Clare ; Cliff, Peter ; Courtenay, Philip ; Daniel, Richard ; Phillips, Andrea ; Davis, Kate ; Ekins, Andrew ; Grennan, Simon ; Griffiths, David ; Gupta, Sunil ; Hall, Sharon ; Howell, Anthony ; etc.
Post-morality : Cambridge Darkroom and Kettle's Yard 1990 open exhibition, Cambridge Darkroom, Cambridge / Kettle's Yard, Cambridge, 10 November, 1990 - 6 January, 1991
boek